Photocatalytic Nanoparticulate ZrxTi1‐xO2 Coatings with Controlled Homogeneity of Elemental Composition. Issue 39 (24th October 2018) - Cheng, Khley; Chhor, Khay; Passarello, Jean‐Philippe; Colbeau‐Justin, Christophe; Kanaev, Andrei
Abstract: The mixed oxide Zrx Ti1‐x O2 nanoparticulate photocatalysts of different compositions (0≤x≤1) were prepared via sol‐gel method in a rapid micromixing reactor followed by chemical colloid deposition on borosilicate glass beads, drying and heat treatment at temperatures between 400 to 650 °C. The point‐like reaction conditions in the regime of low Damköhler numbers resulted in nucleation of size‐selected reactive zirconium‐titanium oxo‐alkoxy (ZTOA) nanoparticles from zirconium (IV) propoxide and titanium (IV) isopropoxide precursors, which enable strong covalent bonds with hydrophilic supports. The ZTOA nanoparticles with compositions 0≤x≤0.2 convert after a heat treatment to nanoporous monocrystals in distorted anatase phase. The photocatalytic activity of the prepared nanoparticulate coatings on gaseous ethylene decomposition attained maximum at x=0.043 after heat treatment at 500 °C, which was two times higher than that of pure anatase TiO2 . A net correlation between the material photocatalytic activity and amplitude of the slow power decay of photoinduced charges was observed. A model is proposed explaining the power law decay by a thermal release of the localised charges from shallow surface Urbach states. The number density of these states is connected to the specific surface area of the photocatalyst. Abstract : The mixed metal oxide Zr0.05 Ti095 O2 photocatalyst prepared of size‐selected nanoparticles with the optimal elemental composition and crystallinity showed a high photocatalytic activity. This activity correlates with the amplitude of the slow TRMC (Time‐Resolved Microwave Conductivity) decay component, which is explained by the participation of shallow surface Urbach states.